Exploring the linguistic landscape: the case of the ‘Golden Triangle’ in the Algarve, Portugal - Torkington, Kate (2012)
Studies of the linguistic landscape (LL) are concerned with language in its written form, in the public sphere; language that is visible to all through texts such as billboards and other public signs. The LL is such a taken-for-granted part of our everyday experience that its importance as a form of social practice is often overlooked. Taking a mixed methods approach to the case of the linguistic landscape of the ‘Golden Triangle’, an area of tourist resorts which is gradually becoming a residential area in the Algarve, Portugal, I suggest that the discursive construction of a place is partly achieved through the highly visible texts of the LL which may also impact upon the discursive construction of the collective identities of those who inhabit the place.